Congenital left atrial wall aneurysm in a patient with neurofibromatosis. Issue 3 (March 1988) - Uren, N; Been, M; Guzman, F
Abstract : A congenital intrapericardial aneurysmal dilatation of the left atrial wall was found in a 28 year old man who presented with atrial fibrillation after a syncopal event. The patient had cutaneous manifestations of neurofibromatosis. The diagnosis was made by cross sectional echocardiography and confirmed by angiocardiography. Surgical excision of the aneurysm resolved the symptoms.